On Board Computation of Base Products for Rain Characteristics with Pulse Pair Algorithm - Murthy, D.V.N.S.N.; Kishore, J. Krishna; Varaprasad, B.K.S.V.L. (2022 First International Conference on Electrical, Electronics, Information and Communication Technologies (ICEEICT), 2022)
Spacecraft based Doppler radar missions for rain characteristics have an advantage over ground based Doppler Weather Radars (DWRs) as they provide an advance estimate of cyclone origin locations. This will give more lead time to enable people living in the cyclone zone to be relocated sooner to safer locations to minimize loss of life. Additionally, they can aid in better estimation of the vertical integrated liquid profile of rain, ice in clouds, etc. The pulse pair algorithm has been used to process data in ground based DWR for estimating rain characteristics. It is also being considered in emerging spacecraft based radar missions to process the received data in the ground segment to estimate rain characteristics. In this study, the implementation of the pulse pair algorithm in a Field Programmable Gate Array (FPGA) for estimation of the base products for rain characteristics is studied for its potential on board realization. The preliminary analysis and experimental results are encouraging. Additional benefits include reduced downlink data, ease of data transmission and the possibility of direct delivery to end users, where the primary and derived products can be computed for rain characteristics. It also has scope for a potential small satellite mission based on Doppler radar with on board processing that can be launched by a small satellite launch vehicle to reduce the overall cost.